PENDIDIKAN ISLAM DI BELANDA - Marsiyeh Marsiyeh; Tri Lestari (Jurnal Salome : Multidisipliner Keilmuan, 2023)
Islamic education serves as a cornerstone in transmitting religious beliefs, values, and practices within Muslim communities globally. In contemporary times, the landscape of Islamic education is evolving to address the complex challenges posed by modernity, globalization, and diverse educational paradigms. Moreover, Islamic education is not confined to formal institutions but extends to informal settings such as family, community, and digital spaces. Thus, a holistic approach to Islamic education involves collaboration among various stakeholders, including educators, parents, religious leaders, and policymakers, to ensure a comprehensive and integrated learning experience. This abstract presents a synthesis of key themes and considerations within the discourse of Islamic education. Islamic education in the Netherlands today reflects the broader context of multiculturalism, integration, and religious diversity within Dutch society. Because of the constitutional freedom of education in the Netherlands, everyone can set up a school and is entitled to full state funding. There are currently 52 Islamic primary schools, with about 12,500 students mostly of Turkish and Moroccan descent. They focus on the development of Islamic religious identity, and high quality of education as well as student achievements.